What counts? Defining scholarship in continuing professional development using a national modified Delphi study - Soleas, Eleftherios K; Cook, Clare; Chan, Teresa M; Miller, Stephen G (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2026)
Background: In many domains within medical education, scholarship can have unique attributes. The accreditation standards for Canadian Continuing Professional Development (CPD) require scholarly output from each Office in Canada. However, it is unclear what scholarly outputs might be considered as CPD scholarship.Methods: Representatives from a national cross-section of collaborators within the Association of Faculties of Medicine of Canada (AFMC) Continuing Professional Development (CPD) network and other national organizations assisted in this project. Collaborators participated in a 3-phase, modified Delphi study from October 31st, 2023- June 17th, 2024. The three phases included: 1) Registration and Ideation; 2) Consensus Process; 3) Group Validation.Results: A total of 31 individuals registered as part of the consensus panel, and 29 individuals (93.5% response) completed the 3-stages of the modified Delphi. The endorsement of 18/31 types of scholarship, including novel forms such as Community Engagement, Testing/Pilot Approaches, and Advocacy Scholarship, reflects an important shift in how CPD scholarship is understood.Discussion: In a first for our field, the results of this study comprise a consensus-based definition that defines CPD scholarship at a national scale. The results crucially inform national accreditation processes, strategic planning exercises, and overall, in expanding the types and acceptance of activities as recognized scholarly work for those seeking recognition and promotion within the domain of CPD. We do so with the voice of our community to inspire new and emergent scholarship. Periodic reviews of these concepts should be conducted, as scholarly pursuits evolve over time.